Developing Kinesthetic Classrooms to Promote Active Learning. Issue 6 (23rd July 2020) - Culp, Brian; Oberlton, Mia; Porter, Kandice
Abstract: The use of kinesthetic movement in the classroom toward improving health and educational outcomes among youth has been a topic of discourse in recent years. School initiatives that have infused movement as part of the curriculum have shown to increase efficiency in learning, while decreasing stress and contributing to a positive classroom climate. One question that is worthy of exploration pertains to how future professionals in the fields of physical education and health can promote kinesthetic movement in schools and communities. This article discusses how a university kinesthetic classroom prepares future professionals to be advocates for school health using active learning strategies.